Research methodology in strategy and management. Vol. 2 - Ketchen, David J.; Bergh, Donald D. (Research methodology in strategy and management., 2005)
Research methods present the strategic management field with great opportunities and challenges. This second volume of Research Methodology in Strategy and Management includes three types of chapters. One set of chapters describes challenges and opportunities inherent in particular content areas, including resource-based theory, strategic groups research, entrepreneurship, real options, and the construct of performance. A second group of chapters examine key ontological and epistemological issues in the strategic management context, including the relationship between theory and method, the human side of research methods, and mixed-level research. A final group of chapters describe how strategy researchers can better use particular methods. These methods include meta-analysis, Internet-based surveys, and cognitive mapping techniques. Collectively, the chapters offer state of the art thinking about research methodology provided by intellectual leaders within the management field.